Classification-based Planning of Smart Service Portfolios - Frank, Maximilian; Rabe, Martin; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen; Hennig-Cardinal von Widdern, Nils; Reinhold, Jannik (Proceedings of the ISPIM connects)
Smart Services are digital, IT-based services that are using data of a corresponding physical product, e.g. predictive maintenance or automated reordering of consumables for a production machine. This contribution shows a study about 265 services from the German manufacturing industry. We derive hypothesis for identifying Smart Services as well as eleven variables and their 47 characteristics to systematically describe them. A clustering of the found Smart Services resulted in four distinguishable groups. Furthermore, we show statistics of how companies combine the characteristics of their market offerings. Our findings reflect where the theoretical possibilities were fully met by the implementations of the German manufacturing companies and where the industry is still lagging behind. Finally, we derived six bundles of highly consistent combinations of the characteristics. These bundles can be starting points for developing Smart Services for one’s specific use case.

Intelligente Arbeitsvorbereitung auf Basis virtueller Werkzeugmaschinen - Dangelmaier, Wilhelm; Gausemeier, Jürgen (Intelligente Technische Systeme – Lösungen aus dem Spitzencluster it’s OWL)

Innovationen für die Märkte von morgen - Strategische Planung von Produkten, Dienstleistungen und Geschäftsmodellen - Gausemeier, Jürgen; Dumitrescu, Roman; Echterfeld, Julian; Pfänder, Tomas; Steffen, Daniel; Thielemann, Frank

Nationales Kompetenz-Monitoring - Bericht: Energiespeichersysteme (Fokus Lithium-Ionen-Speicher) - Gausemeier, Jürgen; Guggemos, Michael; Kreimeyer, Andreas; Lange, Thomas; Behrens, Jan Henning; Seitz, Ralph; Ortloff, Luise; Frey, Anna; Dachsberger, Stephanie; Drewel, Marvin; Frank, Maximilian

Verbraucherbildung als Bildung für Lebensführung - Schlegel-Matthies, Kirsten (Verbraucherbildung: Ein weiter Weg zum mündigen Verbraucher)

Haushaltsbezogene Bildung – quo vadis? Daseinsvorsorge und Lebensführung im Wandel - Schlegel-Matthies, Kirsten (Haushalt in Bildung & Forschung)
Der Beitrag geht der Frage nach, wie haushaltsbezogene Bildung als Ernährungs- und Verbraucherbildung umgesetzt werden kann, damit Jugendliche selbstbestimmt und verantwortlich ihre individuellen Vorstellungen von einem „guten“ und „gelingenden“ Leben umsetzen können. Die Auseinandersetzung mit dem Zusammenwirken von gesellschaftlicher Lebensweise, privater Lebensführung und individuellen Lebensstilen erweist sich dabei als bedeutsam.

High-Speed-Extrusion amorpher Polymere am Beispiel von Polycarbonat (PC) und Polymethylmethacrylat (PMMA) - Pohl, Max

Simulation und Modellierung des Druckverlustes industrieller Polymerschmelzefilter in Abhängigkeit verschiedener Prozessbedingungen sowie deren verschmutzung - Meilwes , Peter

Experimentelle und modellbasierte Analyse der Prozessphasen des Spritzgießsonderverfahrens GITBlow - Landgräber, Björn

Beitrag zur Erhöhung der Wirksamkeit der Faserverstärkung in der Schweißnaht faserverstärkter Thermoplaste - Fiebig, Isabel

Verfahrenstechnische Entwicklung des Direktinjektion-Plasmaverfahrens im Spritzgießprozess - Nordmeyer, Timo

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: A Systematic Review and Updated Meta-Analyses of Prospective Cohort Studies - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
Published meta-analyses indicate significant but inconsistent incident type-2 diabetes (T2D)-dietary glycemic index (GI) and glycemic load (GL) risk ratios or risk relations (RR). It is now over a decade ago that a published meta-analysis used a predefined standard to identify valid studies. Considering valid studies only, and using random effects dose–response meta-analysis (DRM) while withdrawing spurious results (p < 0.05), we ascertained whether these relations would support nutrition guidance, specifically for an RR > 1.20 with a lower 95% confidence limit >1.10 across typical intakes (approximately 10th to 90th percentiles of population intakes). The combined T2D–GI RR was 1.27 (1.15–1.40) (p < 0.001, n = 10 studies) per 10 units GI, while that for the T2D–GL RR was 1.26 (1.15–1.37) (p < 0.001, n = 15) per 80 g/d GL in a 2000 kcal (8400 kJ) diet. The corresponding global DRM using restricted cubic splines were 1.87 (1.56–2.25) (p < 0.001, n = 10) and 1.89 (1.66–2.16) (p < 0.001, n = 15) from 47.6 to 76.1 units GI and 73 to 257 g/d GL in a 2000 kcal diet, respectively. In conclusion, among adults initially in good health, diets higher in GI or GL were robustly associated with incident T2D. Together with mechanistic and other data, this supports that consideration should be given to these dietary risk factors in nutrition advice. Concerning the public health relevance at the global level, our evidence indicates that GI and GL are substantial food markers predicting the development of T2D worldwide, for persons of European ancestry and of East Asian ancestry.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: Assessment of Causal Relations - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
While dietary factors are important modifiable risk factors for type 2 diabetes (T2D), the causal role of carbohydrate quality in nutrition remains controversial. Dietary glycemic index (GI) and glycemic load (GL) have been examined in relation to the risk of T2D in multiple prospective cohort studies. Previous meta-analyses indicate significant relations but consideration of causality has been minimal. Here, the results of our recent meta-analyses of prospective cohort studies of 4 to 26-y follow-up are interpreted in the context of the nine Bradford-Hill criteria for causality, that is: (1) Strength of Association, (2) Consistency, (3) Specificity, (4) Temporality, (5) Biological Gradient, (6) Plausibility, (7) Experimental evidence, (8) Analogy, and (9) Coherence. These criteria necessitated referral to a body of literature wider than prospective cohort studies alone, especially in criteria 6 to 9. In this analysis, all nine of the Hill’s criteria were met for GI and GL indicating that we can be confident of a role for GI and GL as causal factors contributing to incident T2D. In addition, neither dietary fiber nor cereal fiber nor wholegrain were found to be reliable or effective surrogate measures of GI or GL. Finally, our cost–benefit analysis suggests food and nutrition advice favors lower GI or GL and would produce significant potential cost savings in national healthcare budgets. The high confidence in causal associations for incident T2D is sufficient to consider inclusion of GI and GL in food and nutrient-based recommendations.

Developmental trajectories of body mass index from childhood into late adolescence and subsequent late adolescence–young adulthood cardiometabolic risk markers - Oluwagbemigun, Kolade; Buyken, Anette; Alexy, Ute; Schmid, Matthias; Herder, Christian; Nöthlings, Ute (Cardiovascular Diabetology)

Chancen des digitalen Lernens in der Ganztagsschule - Eickelmann, Birgit; Drossel, Kerstin (Jahrbuch Ganztagsschule 2019/20)

Potenziale der Tabletnutzung im Unterricht zur individuellen Förderung – Analysen und Forschungsperspektiven - Drossel, Kerstin; Eickelmann, Birgit (Individuelle Förderung im Unterricht. Empirische Befunde und Hinweise für die Praxis)

Die Implementation digitaler Medien gestalten: zur Bedeutung der Einstellungen von Fremdsprachenlehrkräften - Drossel, Kerstin; Eickelmann, Birgit (Lehrer. Bildung. Gestalten. Beiträge zur empirischen Forschung in der Lehrerbildung)

Soziale Herkunft und computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich - Senkbeil, Martin; Drossel, Kerstin; Eickelmann, Birgit; Vennemann, Mario (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Nutzung digitaler Medien und Prädiktoren aus der Perspektive der Lehrerinnen und Lehrer im internationalen Vergleich - Drossel, Kerstin; Eickelmann, Birgit; Schaumburg, Heike; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Digitalisierung im deutschen Bildungssystem im Kontext des Schulreformdiskurses - Eickelmann, Birgit; Drossel, Kerstin (Schulreform – Zugänge, Gegenstände, Trends)

Berufliche, pädagogische und didaktische Professionalisierungsmaßnahmen in der Sekundarstufe im Zeitalter der Digitalisierung und der Zusammenhang mit der Förderung digitaler Kompetenzen von Schülerinnen und Schülern - Drossel, Kerstin; Eickelmann, Birgit; Port, Sonja; Lorenz, Ramona (Transfer zwischen Lehrer(fort)bildung und Wissenschaft)

Digitalisierung und Bildungsgerechtigkeit – die schulische Perspektive - Drossel, Kerstin; Eickelmann, Birgit; Vennemann, Mario (DDS – Die Deutsche Schule)

Was bedeutet die Digitalisierung für die Lehrerfortbildung? – Ausgangslage und Perspektiven - Eickelmann, Birgit; Drossel, Kerstin; Port, Sonja (Nachhaltige Professionalisierung für Lehrerinnen und Lehrer: Ideen, Entwicklungen, Konzepte)

Price competition and the Bertrand model: The paradox of the German mobile discount market - Kaimann, Daniel; Hoyer, Britta (Applied Economics Letters)
We investigate the degree of price competition among telecommunication firms. Underlying a Bertrand model of price competition, we empirically model pricing behaviour in an oligopoly. We analyse panel data of individual pricing information of mobile phone contracts offered between 2011 and 2017. We provide empirical evidence that price differences as well as reputational effects serve as a signal to buyers and significantly affect market demand. Additionally, we find that brands lead to an increase in demand and thus are able to generate spillover effects even after price increase.

Is It Worth the Attention? A Comparative Evaluation of Attention Layers for Argument Unit Segmentation - Spliethöver, Maximilian; Klaff, Jonas; Heuer, Hendrik (Proceedings of the 6th Workshop on Argument Mining)
Attention mechanisms have seen some success for natural language processing downstream tasks in recent years and generated new state-of-the-art results. A thorough evaluation of the attention mechanism for the task of Argumentation Mining is missing. With this paper, we report a comparative evaluation of attention layers in combination with a bidirectional long short-term memory network, which is the current state-of-the-art approach for the unit segmentation task. We also compare sentence-level contextualized word embeddings to pre-generated ones. Our findings suggest that for this task, the additional attention layer does not improve the performance. In most cases, contextualized embeddings do also not show an improvement on the score achieved by pre-defined embeddings.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Schlussbericht zum Vorhaben "Additive Leichtbaustrukturen für Flugzeugkomponenten" : Verbund: KOBFS - Kostenoptimierter Baukasten für Flügelsysteme - Ahlers, Dominik; Tröster, Thomas

The Other Side of the Same Coin – How Communal Beliefs About Entrepreneurship Influence Attitudes Toward Entrepreneurship - Jakob, Eva Alexandra; Isidor, Rodrigo; Holger, Steinmetz; Marius, Wehner; Kabst, Rüdiger (Journal of Vocational Behavior)

The Contextual Role of Regulatory Stakeholder Pressure in Proactive Environmental Strategies: An Empirical Test of Competing Theoretical Perspectives - Jakob, Eva Alexandra; Baum, Matthias; Huett, Pascal; Kabst, Rüdiger (Organization & Environment)

Nationale Forschungsdateninfrastruktur, die Initiative NFDI4Culture und die Musikwissenschaft - Pasdzierny, Matthias; Röwenstrunk, Daniel; Schmidt, Dörte (Die Musikforschung)

Fokusthemen und Aufgabenbereiche für eine Forschungsdateninfrastruktur zu materiellen und immateriellen Kulturgütern. Living Document der NFDI-Initiative NFDI4Culture. - Altenhöner, Reinhard; Bicher, Katrin; Bracht, Christian; Brand, Ortrun; Blümel, Ina; Bulle, Klaus; Effinger, Maria; Hammes, Andrea; Hartmann, Thomas; Kailus, Angela; Kett, Jürgen; Pittroff, Sarah; et al.

Virtual reality interventions for balance prevention and rehabilitation after musculoskeletal lower limb impairments in young up to middle-aged adults: A comprehensive review on used technology, balance outcome measures and observed effects - Vogt, Sarah; Skjæret-Maroni, Nina; Neuhaus, Dorothee; Baumeister, Jochen (International Journal of Medical Informatics)

Who Sets the Tone? Determining the Impact of Convergence Behaviour Archetypes in Social Media Crisis Communication - Mirbabaie, Milad; Bunker, D.; Stieglitz, S. (Information Systems Frontiers)

‘Silence’ as a Strategy during a Corporate Crisis - The Case of Volkswagen’s ‘Dieselgate’ - Stieglitz, S.; Mirbabaie, Milad; Kroll, T.; Marx, J. (Internet Research)

‘Breaking’ News: Uncovering Sense-Breaking Patterns in Social Media Crisis Communication during the 2017 Manchester Bombing - Mirbabaie, Milad; Marx, J. (Behaviour & Information Technology)

Challenges and Opportunities of Artificial Intelligence for Incident Management - Mirbabaie, Milad; Hellmann, M. (Proceedings of the IFIP 8.2 OASIS Workshop on Post-Digitalization 2019)

Collective Identity Formation on Instagram – Investigating the Social Movement Fridays for Future - Brünker, F.; Deitelhoff, F.; Mirbabaie, Milad (Proceedings of the 30th Australasian Conference on Information Systems)

Reducing the Cognitive Load of Decision-Makers in Emergency Management through Augmented Reality - Mirbabaie, Milad; Fromm, J. (Proceedings of the Twenty-Seventh European Conference on Information Systems)

Nudging People to save Energy in Smart Homes with Social Norms and Self-Commitment - Kroll, T.; Paukstadt, U.; Kreidermann, K.; Mirbabaie, Milad (Proceedings of the Twenty-Seventh European Conference on Information Systems)

'Show Me Your People Skills' - Employing CEO Branding for Corporate Reputation Management in Social Media - Mirbabaie, Milad; Marx, J.; Stieglitz, S. (Proceedings of the 14th International Conference on Wirtschaftsinformatik)

The Potential of Augmented Reality for Improving Occupational First Aid - Fromm, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 14th International Conference on Wirtschaftsinformatik)

Impact of Al Activators on Structure and Catalytic Performance of Cr Catalysts in Homogeneous Ethylene Oligomerization – A Multitechnique in situ/operando Study - Grauke, Reni; Schepper, Rahel; Rabeah, Jabor; Schoch, Roland; Bentrup, Ursula; Bauer, Matthias; Brückner, Angelika (ChemCatChem)

The effect of organizational support on whistleblowing behavior - An experimental analysis - Protte, Marius

Population Dynamics of Tax Avoidance with Crowding Effects - Lorenz, Johannes (Journal of Evolutionary Economics)
There are two ways for taxpayers to avoid paying taxes: legal tax optimization and illegal tax evasion. The government reacts by altering the law, and by conducting audits, respectively. These phenomena are modeled as a strategic interaction between all taxpayers: the more taxpayers optimize, the lower the optimization result as a consequence of the government tightening the tax law. The more taxpayers evade, the higher the risk of detection because of the tax agencies increasing the audit probability. It emerges that, in equilibrium, the population shares of optimizers and evaders are not interdependent; rather, they both increase to the detriment of the share of non-optimizing taxpayers. If the government reacts to changed optimization behavior with too large a delay, an equilibrium tax law cannot be reached. Tax codes should be updated rapidly in order to avoid a permanent change of the tax law, which is costly both for the legislator and the taxpayers facing legal uncertainty.

Was lange währt, wird endlich gut? Vorschau zur erwarteten Rechtsprechung des BFH zur grunderwerbsteuerlichen Konzernklausel - Kittl, Maximilian; Lorenz, Johannes (Deutsches Steuerrecht)

Tax Complexity for Multinational Corporations in South Africa - Evidence from a Global Survey - Hoppe, Thomas; Safaei, Reyhaneh; Singleton, Amanda; Sureth-Sloane, Caren (Tax Simplification - An African Perspective)
This chapter examines the drivers of corporate income tax complexity for multinational corporations in South Africa. Based on unique data from a global survey of tax consultants which was conducted in 2016 by Hoppe et al, novel insights can be provided into the complexity of the South African tax system. The data enable a comparison of South Africa with the global mean of tax complexity, as well as with its major trade and investment partners. It is further possible to distinguish between different areas of tax complexity, ie, tax code complexity (complexity inherent in the different regulations of the tax code) and tax framework complexity (complexity that arises from the features and processes of a tax system). Frequent changes in tax regulations, ambiguity and interpretation, as well as record-keeping, are found to be the most important complexity drivers in the tax code of South Africa. The analysis further highlights that anti-avoidance provisions, such as transfer pricing and controlled foreign corporation rules, are perceived as most complex. With respect to tax framework complexity, the poor disclosure of audit selection criteria, the lack of experience or technical skills of tax officers in the audit process and problems associated with tax refunds appear to be serious concerns. Even though South Africa’s overall tax system complexity does not seem to differ very much from other related countries, a closer look into the details reveals a number of future challenges.

Inheritance Tax Planning with Uncertain Future Payroll Expenses: An Analytical Solution to the Optimal Choice between Full and Standard Exemption - Diller, Markus; Späth, Thomas; Lorenz, Johannes (Journal of Business Economics)
Under the German Inheritance Tax and Gift Tax Act, the transfer of business assets can be exempted from taxation up to 100%. However, this exemption depends on the evolution of the company’s payroll, which is highly uncertain. We model the uncertain nature of payroll evolution using a Geometric Brownian motion. We obtain closed-form solutions for the expected effective exemption and for the expected effective tax rate. We find that the uncertainty effect is most pronounced for moderate negative and positive growth rates. Furthermore, higher uncertainty reduces the value of the effective tax exemption. Also, we find that the (partially progressive) German inheritance tax function by trend promotes standard exemption. The results enable tax planners to make an optimal choice between standard or full exemption and allow for calculating the expected tax burden.

Deep drawing of fiber metal laminates for automotive lightweight structures - Heggemann, Thomas; Homberg, Werner (Composite Structures)
Current challenges in the automotive industry are the reduction of fuel consumption and the CO2 emissions of future car generations. These aims can be achieved by reducing the weight of the car, which further improves the driving dynamics. In most currently mass-produced cars, the body accounts for one of the largest parts by weight, and hence designing a lightweight car body assumes great importance for reducing fuel consumption and CO2 emissions. Extremely lightweight designs can be achieved by using purely composite materials, which are very light but also highly cost intensive and not yet suitable for large scale production due to the necessity of manual processing. A promising approach for the automated, large-scale production of lightweight car structures with a high stiffness to weight ratio is the combination of high strength steel alloys and CFRP prepregs in a special hybrid material/fiber metal laminate (FML) – which can be further processed by forming technologies such as deep drawing. In current research work at the Chair of Forming and Machining Technology (LUF) at the University of Paderborn, innovative manufacturing processes are being developed for the production of high strength automotive structural components made of fiber metal laminates. This paper presents the results of technological and numerical research that is currently being performed at the LUF into the forming of hybrid fiber metal laminates. This paper focuses on the results of basic research and the individual measures (tool, process and material design) necessary for achieving the desired part quality.

Method of superposing a multiple driven magnetic field to minimize stray fields around the receiver for inductive wireless power transmission - Lange, Sven; Büker, Maik-Julian; Sievers, Denis; Hedayat, Christian; Förstner, Jens; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)
This paper presents a new methodology by using a multiple coil array for energy transmission. The complex current strengths of the transmitting coil array are calculated by having the knowledge about of the mutual inductances and the symmetries of the transmitting coil array, so that its resulting magnetic field mainly penetrates only the receiving coil and is strongly attenuated outside. This method is used for an optimized wireless energy transmission but can also be implemented for other inductive applications.

Numerical simulation of high-speed joining of sheet metal structures - Meschut, Gerson; Hein, David; Gerkens, Michael (Procedia Manufacturing)

Fatigue life investigation of resistance spot-welded dual-and complex-phase steels using the LWF-KS-II concept - Hein, David; Meschut, Gerson; Tümkaya, Gökhan

Inductive Locating Method to Locate Miniaturized Wireless Sensors within Inhomogeneous Dielectrics - Lange, Sven; Schröder, Dominik; Hedayat, Christian; Otto, Thomas; Hilleringmann, Ulrich (2019 17th IEEE International New Circuits and Systems Conference (NEWCAS))
For the measurement of process data in bioreactors, very small wireless sensors are currently under development to replace the conventional rod probes. The so-called Sens-o-Spheres measure the temperature and in future the oxygen content and the pH of fluids. In order to evaluate the distribution of the measured values within the process, it is necessary to locate the wireless sensors. Because of the small size of the sphere (diameter 8 mm), inhomogeneous ambient media and the size of the reactor (less than 2 m), an inductive locating by magnetic fields with a frequency of f = 13.56 MHz is necessary. Since the behaviour of the magnetic field is very different from that of the electromagnetic wave, new locating methods are required, which are presented in this paper.
Keywords: oxygen content; inhomogeneous ambient media; magnetic field; inductive locating method; miniaturized wireless sensors; inhomogeneous dielectrics; conventional rod probes; Sens-o-Spheres measure; frequency 13.56 MHz

Success Factors for the Consolidation and Anchoring of Digitalisation Projects - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Hochschulforum Digitalisierung (2019). Strategies Beyond Borders – Transforming Higher Education in a Digital Age. Book of Abstracts)

Digitalisierungsstrategien auf dem Prüfstand – eine empirische Untersuchung auf Basis der Grounded-Theory-Methodologie an deutschen Hochschulen - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Teilhabe an Bildung und Wissenschaft)

Stellungnahme der DFG-Kommission zur Evaluierung des Förderprogramms „Fachinformationsdienste für die Wissenschaft“ - Oevel, Gudrun

Special issue: Selected papers of BPM 2017 - Carmona, Josep; Engels, Gregor; Kumar, Akhil; Reichert, Manfred (Information Systems)

2019 ACM/IEEE 22nd International Conference on Model Driven Engineering Languages and Systems Companion (MODELS-C) - Engels, Gregor; Burgueno, Loli; Pretschner, Alexander; Voss, Sebastian; Chaudron, Michel; Kienzle, Jörg; Völter, Markus; Gérard, Sébastien; Zahedi, Mansooreh; Bousse, Erwan; Rensink, Arend; Polack, Fiona; et al.

Values in Computing (Dagstuhl Seminar 19291) - Engels, Gregor; Becker, Christoph; Feenberg, Andrew; Ferrario, Maria Angela; Fitzpatrick, Geraldine (Dagstuhl Reports 9(7))

Age and tenure diversity on the work floor: Evidence from a natural field experiment in production - Thommes, Kirsten; Klabuhn, Janny (Evidence-based HRM)

Significance and Challenges of Data-driven Product Generation and Retrofit Planning - Massmann, Melina; Meyer, Maurice; Dumitrescu, Roman; Enzberg, Sebastian von; Frank, Maximilian; Koldewey, Christian; Kühn, Arno; Reinhold, Jannik (Procedia CIRP)

Gestaltung hybrider Wertschöpfung und Arbeit im Kontext von Smart Services - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman; Frank, Maximilian; Schweppe, Thomans; Melzer, Annegret (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Strategie als Erfolgsfaktor - Koldewey, Christian; Dumitrescu, Roman (ServiceToday)

Development Process for Smart Service Strategies - Koldewey, Christian; Evers, Hans Heinrich; Dumitrescu, Roman; Frank, Maximilian; Gausemeier, Jürgen; Reinhold, Jannik (Proceedings of The XXX ISPIM INNOVATION CONFERENCE)

Classification-based Planning of Smart Service Portfolios - Frank, Maximilian; Rabe, Martin; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen; Hennig-Cardinal von Widdern, Nils; Reinhold, Jannik (Proceedings of the ISPIM connects)

Fault Tolerant and Fully Dynamic DFS in Undirected Graphs: Simple Yet Efficient - Baswana, Surender; Gupta, Shiv; Tulsyan, Ayush (44th International Symposium on Mathematical Foundations of Computer Science (MFCS 2019))

Grammatikwandel digital-kulturwissenschaftlich erforscht. Mittelniederdeutscher Sprachausbau im interdisziplinären Zugriff - Merten, Marie-Luis; Seemann, Nina; Wever, Marcel Dominik (Niederdeutsches Jahrbuch)

Approaches for Collaborative Security Defences in Multi Network Environments - Koning, Ralph; Polevoy, Gleb; Meijer, Lydia; de Laat, Cees; Grosso, Paola (2019 6th IEEE International Conference on Cyber Security and Cloud Computing (CSCloud)/ 2019 5th IEEE International Conference on Edge Computing and Scalable Cloud (EdgeCom))
Resolving distributed attacks benefits from collaboration between networks. We present three approaches for the same multi-domain defensive action that can be applied in such an alliance: 1) Counteract Everywhere, 2) Minimize Countermeasures, and 3) Minimize Propagation. First, we provide a formula to compute efficiency of a defense; then we use this formula to compute the efficiency of the approaches under various circumstances. Finally, we discuss how task execution order and timing influence defense efficiency. Our results show that the Minimize Propagation approach is the most efficient method when defending against the chosen attack.
Keywords: computer network security; multinetwork environments; multidomain defensive action; task execution order; timing influence defense efficiency; distributed attacks; collaborative security defence approach; minimize propagation approach; minimize countermeasure approach; counteract everywhere approach; Conferences; Cloud computing; Computer crime; Edge computing; Security; Defense Approaches; Multi-Domain Defense; Collaborative Defense; Defense Algorithms; Computer Networks

Lektionen für Alexa & Co?! - Haeb-Umbach, Reinhold (forschung)
Abstract Wenn akustische Signalverarbeitung mit automatisiertem Lernen verknüpft wird: Nachrichtentechniker arbeiten mit mehreren Mikrofonen und tiefen neuronalen Netzen an besserer Spracherkennung unter widrigsten Bedingungen. Von solchen Sensornetzwerken könnten langfristig auch digitale Sprachassistenten profitieren.

Scalable Multi Objective Path Optimization for Multi-Laser Selective Laser Melting Scanning Systems - N., N.

Digitaler Wandel als strategischer Transformationsprozess – zum allgemeinen und hochschulspezifischen Verständnis der Digitalisierung - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie

Museum – Exhibition - Cultural Heritage. Museum – Ausstellung- Kulturelles Erbe. Changing Perspectives from China to Europe. Blickwechsel zwischen China und Europa - Seng, Eva- Maria

乌尔姆设计学院：20 世纪50 至60 年代联邦德国工业设计的训练中心 - The Ulm School of Design: A Training Center for Industrial Design in the Federal Republic of Germany in the 1950/60s - Seng, Eva- Maria (Zhuangshi 7)

包豪斯：20 世纪艺术、设计和建筑领域最具影响力的艺术学院 - Bauhaus: The Most Influential Art School in the Field of Arts, Design and Architecture in the 20th Century - Seng, Eva- Maria (Zhuangshi 11)

- “德国制造”——德意志制造联盟：20 世纪早期的德国工业设计、建筑设计与艺术院校改革 - ‘Made in Germany’- The German Werkbund: Industrial Design, Architecture and Art School Reform in the Early 20th Century - Seng, Eva- Maria (Zhuangshi 6)

The Museum - Seng, Eva- Maria (Tsinghua Art Museum TAM 11)

Geometrische Muster zwischen frühneuzeitlicher Utopie und russischer Avantgarde - Seng, Eva- Maria; Saage, Richard (Bauen mit Sinn. Schritte zu einer Philosophie der Architektur)

Kandidatur zum Bauhüttenwesen Die internationale für das immaterielle Kulturerbe der UNESCO - Seng, Eva- Maria („Genius loci“. Dombaumeistertagung Paderborn 23.-29. September 2018)

Competence-based Planning of Value Networks for Smart Services - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Proceedings of the ISPIM Connects Ottawa – Innovation for Local and Global Impact)

Kinder als Forscher in eigener und gemeinsamer Sache – ein Weg zur Partizipation? Ein kinderrechtebasierter didaktischer Ansatz und dessen Relevanz aus der Perspektive von Grundschulkindern - Hüpping, Birgit; Büker, Petra (Pädagogischer Blick)

Combining Children's Participation Rights in Research with Professionalisation of Educators and Teachers – Critical Analysis of a Transition Study Design - Büker, Petra (The Routledge International Handbook of Young Children’s Rights)

Kompetenzerwerb im Lese- und Literaturunterricht der Grundschule - Büker, Petra; Vorst, Claudia (Lese- und Literaturunterricht)
stark überarbeitete Auflage. (Deutschunterricht in Theorie und Praxis, Bd. 11/2). Baltmannsweiler: Schneider Verlag.

Partizipation von Kindergarten- und Grundschulkindern an Übergangsgestaltung, Übergangsforschung und am Transfer in optimierte Praxis: Erfahrungen aus der Kinderbefragungsstudie „buddY“. - Büker, Petra (Grundschulpädagogik zwischen Wissenschaft und Transfer. Jahrbuch Grundschulforschung)

Children’s voices as a bridge between educators in kindergarten and teachers in primary school: Potential of children’s perspectives to support professional development - Büker, Petra; Höke, Julia (Listening to children’s advice about starting school and school age care. EECERA Book Series: Towards an Ethical Praxis in Early Childhood: From Research into Practice)

Big Data: Sublinear Algorithms for Distributed Data Streams - Malatyali, Manuel

Perspektiven des Transfers von Forschungsbefunden im Übergang Kindergarten-Grundschule - Büker, Petra; Müller, Ulrike Beate; Seifert, Anja; Arndt, Petra; Carle, Ursula; Graf, Ulrike; Kieferle, Christa; Kordulla, Agnes; Sturmhöfel, Nicole; Wehner, Franziska (Grundschulpädagogik zwischen Wissenschaft und Transfer. Jahrbuch Grundschulforschung)

Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen

Grundthemen der Literaturwissenschaft: Literarische Institutionen

Zersetzung. Automatismen und Strukturauflösung
Erscheinungsjahr in Klammern: 2018

Die Explosion der Bilder im Kopf oder: „Les beaux livres sont écrits dans une sorte de langue étrangère.“ - Eke, Norbert Otto (Werner Fritsch: Faust Sonnengesang II und III. Materialien)

„Es ist nur eine Probe.“ George Taboris ‚musikalisches Opfer‘ „Die Goldberg-Variationen“ - Eke, Norbert Otto (Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen)

Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen biblischer Texte - Eke, Norbert Otto; Strotmann, Angelika (Davidfigur und Opfermotiv – Jüdisch-christliche Transformationen)

Literarische Institutionen - Eke, Norbert Otto; Elit, Stefan (Grundthemen der Literaturwissenschaft: Literarische Institutionen)

Historischer Abriss: Aufklärung bis Gegenwart - Eke, Norbert Otto (Grundthemen der Literaturwissenschaft: Literarische Institutionen)

Zersetzung(en) dramatischer Ordnung: Marlene Streeruwitz und Rainald Goetz - Eke, Norbert Otto (Zersetzung. Automatismen und Strukturauflösung)
Erscheinungsjahr in Klammern: 2018

Zersetzung. Automatismen und Strukturauflösung - Eke, Norbert Otto; Hohlweck, Patrick (Zersetzung. Automatismen und Strukturauflösung)
Erscheinungsjahr in Klammern: 2018

Auslegungsmethode für zyklisch beanspruchte Stahl/CFK-Klebverbindungen unter besonderer Berücksichtigung des Rissfortschritts - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (19. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Design concept for adhesively bonded steel/CFRP structures under cyclic loading - Kowatz, Jannik; Meschut, Gerson (AJP2019 - 1st International Conference on Advanced Joining Processes - Book of Abstracts)

Approximate bound state solutions of the Klein-Gordon equation with the linear combination of Hulthén and Yukawa potentials - Ahmadov, A.I.; Aslanova, S.M.; Orujova, M.Sh.; Badalov, S.V.; Dong, Shi-Hai (Physics Letters A)

A possibilistic finite element method for sparse data - Dridger, A.; Caylak, Ismail; Mahnken, R.; Penner, Eduard (Safety and Reliability)

Stress-based fatigue life prediction of adhesively bonded hybrid hyperelastic joints under multiaxial stress conditions - Çavdar, Serkan; Teutenberg, Dominik; Meschut, Gerson; Wulf, A.; Hesebeck, O.; Brede, M.; Mayer, B. (International Journal of Adhesion and Adhesives)